2015
DOI: 10.1007/s00289-015-1411-7
|View full text |Cite
|
Sign up to set email alerts
|

Lignin as coupling agent in EPDM rubber: thermal and mechanical properties

Abstract: EPDM rubbers were prepared and the effect of lignin as coupling agent was investigated by means of mechanical and thermal properties. As a contrast, using vinyl triethoxy silane (VTS) coupling agent in EPDM rubber was also studied. The median diameter and the specific surface area of lignin used were 6.61 lm and 722.24 m 2 kg -1 , respectively. Properties of EPDM rubbers were assessed by tensile testing, thermogravimetric analysis (TG/DTG) and scanning electron microscopy (SEM). The results showed that using l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…As shown in Figure S6 , the tensile strength and tear strength of NRL increased along with the MSLS contents, in which the maximum value was reached when the content was 1.5 phr while the corresponding tensile strength and tear strength were 32.33 MPa and 48.37 KN m −1 , respectively ( Table S3 ). Compared with NRL without MSLS, a significant enhancement in mechanical properties was realized, indicating that carboxylated lignin had a reinforcing effect in NRL since it can work as a considerable filler for polymer matrix, and the compatibility with rubber matrix may also be enhanced, as confirmed by the above water contact angle test [ 32 , 33 , 34 ]. Subsequently, PAE was added under a fixed MSLS content of 1.5 phr to construct a stiff and double network with MSLS for the further improvement of mechanical properties [ 35 ].…”
Section: Resultsmentioning
confidence: 92%
“…As shown in Figure S6 , the tensile strength and tear strength of NRL increased along with the MSLS contents, in which the maximum value was reached when the content was 1.5 phr while the corresponding tensile strength and tear strength were 32.33 MPa and 48.37 KN m −1 , respectively ( Table S3 ). Compared with NRL without MSLS, a significant enhancement in mechanical properties was realized, indicating that carboxylated lignin had a reinforcing effect in NRL since it can work as a considerable filler for polymer matrix, and the compatibility with rubber matrix may also be enhanced, as confirmed by the above water contact angle test [ 32 , 33 , 34 ]. Subsequently, PAE was added under a fixed MSLS content of 1.5 phr to construct a stiff and double network with MSLS for the further improvement of mechanical properties [ 35 ].…”
Section: Resultsmentioning
confidence: 92%
“…The high surface area GO (>400 m 2 /g) incorporation led to the formation of hydrogen bonding and dipolar interaction with lignin as well as NBR, resulting in nanoscale lignin dispersion in the rubber matrix with a strong reinforcing effect. Unlike traditional filler in rubber composites, lignin has been proven to be an effective coupling agent in EPDM rubber/CB composites by Xu et al 215 . It was observed that the alkali lignin can enhance the inter-phase cohesion between the constituents in the EPDM composites.…”
Section: Lignin/conventional Filler Hybrid Reinforced Rubber Compositesmentioning
confidence: 99%
“…They demonstrated the ability of lignin to simultaneously improve the modulus, strength, and toughness in the lignin/EPDM composites without sacrificing extensibility. In another study, Xu et al (2015) examined lignin as a coupling agent in order to observe the thermal, morphological, and mechanical properties of EPDM rubber in the presence of triethoxy silane. The results revealed that the mechanical properties were better than those of the pure rubber in the presence of triethoxysilane.…”
Section: Introductionmentioning
confidence: 99%